Personality traits and demographic characteristics: a validation study of the Big Five in the Moroccan context - Kh. Chraibi; M. Lamouine; I. Chaker; A. Zahi (Психолого-педагогические исследования)
Context and relevance. This study investigates the Big Five personality traits within the Moroccan context, exploring their relationship with age, gender, and education level. Objective. This study aimed to assess the psychometric properties of the Arabic BFI within the Moroccan population and to explore the relationship between personality traits and various demographic factors. Methods and materials. Using the Arabic version of the Big Five Inventory (BFI), we surveyed 1537 individuals across Morocco. Results. The Arabic BFI displayed acceptable internal consistency (Cronbach's alpha = 0,72), and good convergent and discriminant validity. There were gender differences, with women scoring higher on neuroticism and men scoring higher on openness and conscientiousness. Age showed significant associations, with neuroticism decreasing and extraversion, agreeableness, and conscientiousness increasing as individuals grew older. Conclusions. These findings confirm that the instrument can be used in Arabic-speaking populations and provide valuable insights into the nature of personality traits within the Moroccan population in the North African context.